Urban Growth Management System for Sample Cities of Turkey and Istanbul - Seydanlioglu, Ahmet; Turgut, Sirma (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
Urban growth management ensures healthy development in urban areas that transform quickly. Urban growth management does not have any marketing goals; the goal is to establish the necessary relation among planning, space, and users. The most common objective of urban growth management is a sustainable urban future to ensure a balance. Planning and management problems are solved by urban growth management system. An urban growth management system includes an urban growth management department and spatial data infrastructure of the urban growth management and portal software.
Keywords: Growth management; urban growth/development; urban growth management; Architecture